Planting Values, Reaping Harmony: Ecological Praxis and Religious Moderation in an Indonesian Eco-Pesantren - Ahkmad Fatoni; Bambang Irawan (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2025)
The ecological crisis and increasing social vulnerability caused by climate-related disasters indicate that environmental stewardship cannot be approached solely as a technical agenda, but must also be grounded in value-based and practice-oriented education. This article examines Pesantren Ekologi Ath-Thaariq in West Java as a case of an Indonesian eco-pesantren where ecological praxis serves as a formative medium for religious moderation. Employing a qualitative case-study design, the study draws on field observations, in-depth interviews with eight informants (caretakers, teachers, students, and non-Muslim visitors), and document analysis of the pesantren’s curriculum and interfaith ecological programs. Data were analyzed using reflexive thematic analysis. The findings show that religious moderation at Ath-Thaariq is not primarily transmitted through doctrinal instruction, but emerges as a habitus shaped through ecological labor, everyday ethics of sharing, and action-based interfaith engagement. Programs that frame nature as a shared home “one roof, one air, one earth”, enable participants from different religious backgrounds to collaborate as co-stewards of the environment. This study contributes to discussions on religious moderation by demonstrating how ecological praxis functions as a lived ethical framework that fosters interfaith solidarity and collective responsibility in responding to ecological challenges.